Lusitropic effects of α- and β-adrenergic stimulation in amphibian heart - Vila Petroff, Martín Gerardo (1994)
The effects ofl 3 and ct-adrenergic stimulation in amphibian superfused hearts and ventricular strips were studied. Superfusion with 3 • 10 .8 M isoproterenol produced a positive inotropic effect, as detected by a 92 + 24% increase in the maximal rate of contraction (+T) and a positive lusitropic effect characterized by a decrease in both the ratio +'F/-i" (23 + 5%) and the half relaxation time (tt/2) (19 + 4%). The mechanical behavior induced by the [3-agonist was associated with an increase in the intracellular cAMP levels from control values of 173 + 19 to 329 + 28 nmol/mg wet tissue. Hearts superfused with 32p in the presence of isoproterenol showed a significant increase in Tn 1 phosphorylation (from 151 + 13 to 240 + 44 pmo132p/mg MF protein) without consistent changes in phosphorylation of C-protein. In sarcoplasmic reticulum membrane vesicles, no phospholamban phosphorylation was detected either by [3-adrenergic stimulation of superfused hearts or when phosphorylation conditions were optimized by direct treatment of the vesicles with cAMP-dependent protein kinase (PKA) and [y 32p] ATE The effect ofct-adrenergic stimulation on ventricular strips was studied at 30 and 22~ At 30~ the effects of 10 5 to 104M phenylephrine on myocardial contraction and relaxation were diminished to non significant levels by addition of propranolol. At 22~ blockage with propranolol left a remanent positive inotropic effect (10% of the total effect ofphenylephrine) and changed the phenylephrine-induced positive lusitropic effect into a negative lusitropic action. These propranolol-resistant effects were abolished by prazosin. Our results suggest that in amphibian heart, both the inotropic and lusitropic responses to catecholamines are mainly due to a [3-adrenergic stimulation which predominates over the ct-adrenergic response. Phospholamban phosphorylation seems not to be involved in mediating the positive lusitropic effect of [3-adrenergic agents whereas phosphorylation oftroponin I may play a critical role. (Mol Cell Biochem 141: 87-95, 1994).